PUSAT PEMBINAAN TUNA NETRA DAN TUNA RUNGU UNTUK ANAK DAN REMAJA DI SURAKARTA DENGAN PENERAPAN METODE TERAPI BERMAIN MELALUI ASPEK PSIKOLOGI RUANG - Adecya Louis Azzahro; Dwi Hedi Heriyanto; Maya Andria (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Regional Regulation No. 2 of 2008 on Disability Equality settled in Surakarta into its own impetus to pay attention to the lives of children with disabilities are no exception blind and deaf. Limitations within visual and hearing impairments make them private closed and not confident, so that the development of impaired social function.Guidance is structured and carried out gradually expected to maximize growth and development of the child to be able to live independently in the community. Methods of play therapy is used as a strategy in the guidance effort. Stages of guidance and environmental comfort to be a reference in the planning and design decisions of Blind and Deaf Rehabilitation Center for Child and Adolescent. The purpose of this design is a manifestation of development activities of the needs of blind and deaf as a disabled people. Design issues are: how to design a coaching center for the blind and deaf are concerned with the psychological comfort using Behavioral Architecture considerations as design approach. The results obtained by the design of the building and area coaching blind and deaf conducive, attractive, and accessible to the consideration of Architecture Behavior. Keywords: Blind, Deaf, Blind and Deaf Rehabilitation Center, Play Therapy, Behavioral Architecture, Psychology Aspects of Space